A B C D is a trapezium with A B < C D and A B parallel to C D . Γ is a circle inscribed in A B C D , such that Γ is tangent to all four sides. If A D = B C = 2 5 and the area of A B C D is 6 0 0 , what is the radius of Γ ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
In this solution, there are no assumptions made about where the center of a circle must lie within the isosceles trapezoid. It also does not assume that C G = G D . These are facts that are not immediately true, and need to be established.
Note that you cannot assume that the configuration is a square, as the area is not 2 5 2 = 6 2 5 .
Let the tangent point of AB is P , tangent point of BC is Q , tangent point of CD is R , tangent point of DA is S. And let: AP = x then by tangent line theory AS = x and we know that SD = 25-x , and by tangent line theory we know that DR = 25-x.
Let PB = y , then according to logic that has been mentioned before, we know that BQ = y QC = 25-y and CR = 25-y
Now we use the area of trapezoid ABCD information to get the height of the trapezoid. A r e a = 2 ( A B + C D ) h e i g h t
6 0 0 = 2 ( x + y + 2 5 − x + 2 5 − y ) h e i g h t
1 2 0 0 = 5 0 h e i g h t
h e i g h t = 2 4
And the radius of the circle is = 1 / 2 h e i g h t = 1 2
Since every isosceles trapezoid is symmetric about the common perpendicular to its bases the height of the given trapezoid is 2 r . The area of a trapezoid is given by 2 1 ⋅ h ⋅ ( a + b ) where a and b is the length of the bases and since the area of the trapezoid is 600 we combine to get:
6 0 0 = 2 1 ⋅ 2 r ⋅ ( a + b ) = r ( a + b )
From that we conclude:
r = ( a + b ) 6 0 0 (*)
By the Pitot Theorem the sum of the lengths of the legs are equal to the sum of the length of the bases in an isosceles tangential trapezoid. Therefore:
a + b = 2 5 + 2 5 = 5 0
From (*) we finally get what we want:
r = 5 0 6 0 0 = 1 2 .
The given trapezium is an isosceles trapezium, let C D = 2 y where y is the length of the tangent either from D or C to the circle,also let d be the height of trapezium. let the tangent from D & C meet circle at T & U respectively from above D T = C U = y also A T = B T = 2 5 − y , A B = 2 5 − y + 2 5 − y = 5 0 − 2 y & C D = 2 y from above using area of trapezium = (sum of opposite parallel sides)d/2 = 600 => ( 5 0 − 2 y + 2 y ) d = 6 0 0 => d = 2 4 . If you draw a diagram you can clearly see that this d is nothing but the diameter of the circle hence the radius will be 12.
No correct solution was received. All solutions assumed that diameter of the circle be equal to the height? This is a crucial part of the argument that was swept under the rug via a 'proof by drawing a diagram', which is rarely a proof.
Furthermore, most solutions assumed (without proof) that the tangent from C has the same length as the tangent from D . Why must this be true? This forms a crucial part of their argument, and without an explanation, the solution will be incomplete.
This solution is also shown because of the bad exposition. It is unclear which tangential points T and U are supposed to be, which is made worse by the subsequent typo that A T = B T . This would lead me to conclude that T is the tangential point on C D , thereby making every subsequent statement wrong.
Let E , F , G and H be the points that Γ is tangent to A B , B C , D C and A D , respectively. Let A E = a . By symmetry we have A E = B E and D G = G C . Thus from circle properties, we have A H = A E = B E = B F = a and D H = D G = G C = C F = 2 5 − a .
Let r be the radius of Γ . By symmetry, we have that 2 r is the height of the trapezium. The area of A B C D is 6 0 0 = 2 1 ( A B + D C ) ( 2 r ) = r ( 2 A E + 2 D G ) = r ( 2 a + 5 0 − 2 a ) = 5 0 r . Hence r = 5 0 6 0 0 = 1 2 .
Sir nice solution. I want to improve in geometry, can you tell me some good books for geometry also helpful for mathematical olympiads?
waiting for reply.
Problem Loading...
Note Loading...
Set Loading...
Let the foot of perpendicular from O to A B , B C , C D , D A be E , F , G , H respectively.
Observe that E O = O H = R (radius of circle), A E = A H (tangents to circle), thus ∠ O E H = ∠ O H E ; thus ∠ A E H = ∠ A H E . Thus A O H and A O E are congruent triangles, which means that they have the same area. Similarly, B O E and B O F , C O F and C O G , D O G and D O H are congruent.
Thus 2 1 ( A D ∗ R ) + 2 1 ∗ ( B C ∗ R ) = 2 1 ( 6 0 0 ) , 5 0 ∗ R = 6 0 0 , so R = 1 2 .